2012
DOI: 10.2807/ese.17.39.20285-en
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a novel human coronavirus by real-time reverse-transcription polymerase chain reaction

Abstract: We present two real-time reverse-transcription polymerase chain reaction assays for a novel human coronavirus (CoV), targeting regions upstream of the E gene (upE) or within open reading frame (ORF)1b, respectively. Sensitivity for upE is 3.4 copies per reaction (95% confidence interval (CI): 2.5-6.9 copies) or 291 copies/mL of sample. No cross-reactivity was observed with coronaviruses OC43, NL63, 229E, SARS-CoV, nor with 92 clinical specimens containing common human respiratory viruses. We recommend using up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
569
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 523 publications
(587 citation statements)
references
References 12 publications
7
569
1
10
Order By: Relevance
“…World health organization (WHO) determined that the pathogen is a novel coronavirus with many similarities to SARS virus (Ge et al, 2013). A British scientist released its complete sequence recently (Corman et al, 2012). Three days later, European Union scientists devised the real-time PCR method to detect this novel coronavirus; this test makes rapid diagnosis possible (WHO, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…World health organization (WHO) determined that the pathogen is a novel coronavirus with many similarities to SARS virus (Ge et al, 2013). A British scientist released its complete sequence recently (Corman et al, 2012). Three days later, European Union scientists devised the real-time PCR method to detect this novel coronavirus; this test makes rapid diagnosis possible (WHO, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…All samples were tested for MERS-CoV by using reverse transcription PCR targeting regions upstream of the envelope gene (6). Respiratory and serum samples from all 7 patients were negative for MERS-CoV.…”
mentioning
confidence: 99%
“…The genetic sequence data indicated that this new coronavirus was a betacoronavirus similar to bat coronaviruses, but not similar to any other coronavirus previously described in humans, including the coronavirus that caused SARS in 2003 [6][7][8]. The available evidence related to this nCoV continued to suggest a zoonotic origin for the virus, and experience with the SARS-CoV also showed that any novel virus that is zoonotic in origin has the potential to efficiently transmit from person to person, especially in healthcare settings, and to cause a global pandemic of severe human illness.…”
Section: Introductionmentioning
confidence: 99%